Mitigation of the tracer impurity accumulation by EC heating in the LHD. (20th September 2016) - Tamura, N; Sudo, S; Suzuki, C; Funaba, H; Nakamura, Y; Tanaka, K; Yoshinuma, M; Ida, K
Abstract: The mitigation of a tracer impurity accumulation in the core region of high-temperature helical plasma was clearly observed by applying electron cyclotron heating (ECH) in the large helical device (LHD). In the LHD, the accumulation of impurities toward the centre of the plasma has been observed in a high-density regime. In this study, for observing clearly the behaviour of impurity ions in the plasma core, the extrinsic 'tracer' impurity was injected into that region by means of a tracer-encapsulated solid pellet (TESPEL). The high-density LHD plasma without ECH definitely shows the strong impurity accumulation, and then it causes the reduction in electron and ion temperatures in the core region. When ECH was applied just after the TESPEL injection, the accumulation of the tracer impurity ions was mitigated. Even after ECH was switched-off, the intensities of the line emissions from the highly-ionized tracer impurity were increased very slightly. The micro-turbulence measurement with a 2-dimensional phase contrast imaging diagnostic during ECH does not support the view that the change in the micro-turbulence would enhance the outward flow (an increase in a diffusive flux, a decrease in an inward convective flux and/or a change the direction of the convective flux from inward to outward) of the impurity ions. Moreover, at this moment, there is no conclusive data regarding a radial electric field measured with a charge exchange spectroscopy diagnostic to support the view that the change in the radial electric field would be attributed to the increment in the outward flow of the impurity ions from the core region of the LHD plasma.